2023
DOI: 10.1093/bib/bbad449
|View full text |Cite
|
Sign up to set email alerts
|

CellTICS: an explainable neural network for cell-type identification and interpretation based on single-cell RNA-seq data

Qingyang Yin,
Liang Chen

Abstract: Identifying cell types is crucial for understanding the functional units of an organism. Machine learning has shown promising performance in identifying cell types, but many existing methods lack biological significance due to poor interpretability. However, it is of the utmost importance to understand what makes cells share the same function and form a specific cell type, motivating us to propose a biologically interpretable method. CellTICS prioritizes marker genes with cell-type-specific expression, using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Hierarchical classification as a NN architectural strategy is in many ways another embodiment of the Coarse-to-Fine perceptual strategy. Specifically, many exciting projects have analogized this idea, by segmenting the task into steps they introspectively perceive their own mind is taking (Wang et al, 2012; Zhu & Bain, 2017; Sarlin et al, 2019), by directly trying to build a system in the style of empirically observed brain structures (Hafner et al, 2017), or even by mimicking behavioral strategies employed by by biologists (Yin & Chen, 2023).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Hierarchical classification as a NN architectural strategy is in many ways another embodiment of the Coarse-to-Fine perceptual strategy. Specifically, many exciting projects have analogized this idea, by segmenting the task into steps they introspectively perceive their own mind is taking (Wang et al, 2012; Zhu & Bain, 2017; Sarlin et al, 2019), by directly trying to build a system in the style of empirically observed brain structures (Hafner et al, 2017), or even by mimicking behavioral strategies employed by by biologists (Yin & Chen, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…The most similar project to our own from the perspective of hierarchical NNs is the CellTICS network by Yin & Chen (2023) which is also an explicitly hierarchical NN designed to distinguish cell classes and cell subclasses via supervised training with pre-labeled scRNAseq data. The authors demonstrate through extensive benchmarking that their cutting edge model is both the best architecture for this task published to date, and is by design interpretable.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations